Bioactive compounds and bioactive properties of chaga (Inonotus obliquus) mushroom: a review - Han Peng; Fereidoon Shahidi (Journal of Food Bioactives, 2020)
Chaga (Inonotus obliquus) is an edible herbal mushroom extensively distributed in the temperate to frigid regions of the Northern hemisphere, especially the Baltic and Siberian areas. Chaga parasites itself on the trunk of various angiosperms, especially birch tree, for decades and grows to be a shapeless black mass. The medicinal/nutraceutical use of chaga mushroom has been recorded in different ancient cultures of Ainu, Khanty, First Nations, and other Indigenous populations. To date, due to its prevalent use as folk medicine/functional food, a plethora of studies on bioactive compounds and corresponding compositional analysis has been conducted in the past 20 years. In this contribution, various nutraceutical and pharmaceutical potential, including antioxidant, anti-inflammatory, anti-tumor, immunomodulatory, antimutagenic activity, anti-virus, analgesic, antibacterial, antifungal, anti-hyperglycemic, and anti-hyperuricemia activities/effects, as well as main bioactive compounds including phenolics, terpenoids, polysaccharides, fatty acids, and alkaloids of chaga mushroom have been thoroughly reviewed, and tabulated using a total 171 original articles. However, only key bioactivities and bioactives are selectively discussed. Besides, the up-to-date toxicity concerns and risk assessment about the misuse of chaga, which limit its acceptance and use as medicinal/ nutraceutical products, have also been clarified.